2018
DOI: 10.1186/s12964-018-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

Fascin induces melanoma tumorigenesis and stemness through regulating the Hippo pathway

Abstract: BackgroundFascin is a F-actin bundling protein and its overexpression is correlated with poor prognosis and increases metastatic potential in a number of cancers. But underlying function and mechanism of fascin on tumorigenesis in melanoma remain elusive.MethodsThe melanoma cell lines WM793 and WM39 were employed for the soft agar and sphere formation assay. Quantitative RT-PCR and Western blot were performed for identifying the gene expression at mRNA and protein levels, respectively. Co-IP and in vitro GST p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 31 publications
1
27
1
Order By: Relevance
“…Later, nesprin‐2 was found to bind to FSCN1 and play a key role in nuclear movement and deformation . Moreover, two serine/threonine kinases (mammalian STE20‐like 1/2; [MST1/2]) and an epithelial‐mesenchymal transition (EMT)‐promoting factor (Snail) were found physiologically interact with FSCN1, and the interaction serves to modulate cancer progression …”
Section: Discussionmentioning
confidence: 99%
“…Later, nesprin‐2 was found to bind to FSCN1 and play a key role in nuclear movement and deformation . Moreover, two serine/threonine kinases (mammalian STE20‐like 1/2; [MST1/2]) and an epithelial‐mesenchymal transition (EMT)‐promoting factor (Snail) were found physiologically interact with FSCN1, and the interaction serves to modulate cancer progression …”
Section: Discussionmentioning
confidence: 99%
“…There are reports indicating that fascin might have actin‐bundling independent functions in cancer [128]. Fascin has been shown to interact with a number of proteins other than F‐actin [24,123,129–131]. Although the functional implication of these interactions in cancer metastasis is largely unclear, we suspect that fascin might have much broader roles in cancer metastasis than promoting cancer cell migration and invasion.…”
Section: Perspective and Future Directionmentioning
confidence: 94%
“…In lung adenocarcinoma, inhibition of OXPHOS abrogates CSC self‐renewal by activation of AMP‐activated kinase and inhibition of Hippo pathway transcription factor YAP1 [113]. Intriguingly, fascin knockdown or knockout also inhibits CSC self‐renewal [22] and decreases YAP1 protein levels [24,123]. It remained to be determined whether fascin might control cancer cell stemness through enhancing mitochondrial metabolism.…”
Section: Mechanisms Underlying Fascin‐mediated Cancer Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports about role of Fascin-1 in the development and metastasis of many neoplasms such as melanoma, breast, lung and stomach cancer [14][15][16][17]. Several studies have shown that increase in expression of Fascin-1 correlates with tumours characterized by high metastatic potential and poor prognosis as well as shorter overall survival [12].…”
Section: Discussionmentioning
confidence: 99%